2007
DOI: 10.1111/j.1349-7006.2007.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Variant genotypes and haplotypes of the epidermal growth factor gene promoter are associated with a decreased risk of gastric cancer in a high‐risk Chinese population

Abstract: Epidermal growth factor (EGF), a ligand of the EGF receptor, plays a critical role in the development of gastric cancer. Genetic variants in its promoter region may influence transcription activity and contribute to gastric cancer predisposition. To test this hypothesis, we genotyped three EGF promoter polymorphisms (G61A, G-1380A, and A-1744G) in a case-control study of 675 gastric cancer cases and 704 cancer-free controls. We found that the variant genotypes of EGF 61GA/AA were associated with a significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
4
28
1
Order By: Relevance
“…19,20 Moreover, this regulation varies according to the arrangements of ligand-receptor engagement, tyrosine phosphorylation and subsequent receptor dimerization We also analyzed the distribution of EGF genotypes among the East Asian population and Caucasian population from the previous studies, and found that, the EGF genotypes were significantly different between the East Asian population and Caucasian population. In this study, the EGF 61A allele frequency (0.273) in control was close to that reported in the Chinese (0.297, 0.305), 14,24 Korean (0.284) 25 and Japanese populations (0.313, 0.304), 12,13 but was significantly lower than that in the Caucasians (higher than 0.500). 10,11,26,27 Therefore, we confirmed that EGF genotypes were significantly different between the East Asian and Caucasian populations.…”
Section: Characteristics Of the Study Populationsupporting
confidence: 86%
“…19,20 Moreover, this regulation varies according to the arrangements of ligand-receptor engagement, tyrosine phosphorylation and subsequent receptor dimerization We also analyzed the distribution of EGF genotypes among the East Asian population and Caucasian population from the previous studies, and found that, the EGF genotypes were significantly different between the East Asian population and Caucasian population. In this study, the EGF 61A allele frequency (0.273) in control was close to that reported in the Chinese (0.297, 0.305), 14,24 Korean (0.284) 25 and Japanese populations (0.313, 0.304), 12,13 but was significantly lower than that in the Caucasians (higher than 0.500). 10,11,26,27 Therefore, we confirmed that EGF genotypes were significantly different between the East Asian and Caucasian populations.…”
Section: Characteristics Of the Study Populationsupporting
confidence: 86%
“…Polymorphisms determining higher level of growth factors and related receptors, which are important to tissue repair, were associated with reduced risk of GC. Such associations were observed for EGF 5 0 UTR 61G4A, 56,58 TGFB1 -509C4T, 60 TGFBR2 -875G4A, 60 and IGFBP3 -202A4C 65 and Gly32Ala. 66 PGC was reported to not only act as a digestive enzyme, but might also be a growth factor during the healing of gastric lesions.…”
mentioning
confidence: 66%
“…Previously, Shahbazi et al identified a G-to-A substitution at position 61 in the promoter region of EGF, and the presence of the variant 61A allele led to a decreased EGF production in peripheral blood mononuclear cells and decreased susceptibility of malignant melanoma [16]. In a case-control study of 675 gastric cancer cases and 704 cancer-free controls, we also found that the variant genotypes of EGF 61GA/AA genotypes were associated with a significantly decreased risk of gastric cancer as compared with 61GG genotype [17].…”
Section: Introductionmentioning
confidence: 76%
“…The EGF G61A was genotyped by the PCR-RFLP assay and the G-1380A and A-1744G variants were genotyped using a PIRA-PCR assay as we previously reported [17]. The PCR primers for the three loci (G61A, G-1380A, and A-1744G) were 5 0 -TGTCACTAAAGG AAAGGAGGT-3 0 (sense), 5 0 -TTCACAGAGTTTAACAG CCC-3 0 (antisense) for G61A; 5 0 -CCTTCCATTGCTGT CATCCG-3 0 (sense), 5 0 -CATTGCTTTCTGGACTGAGT CAGA-3 0 (antisense) for G-1380A; and 5 0 -AGAGCTAC CCAACTGGGAAGGATCT-3 0 (sense), 5 0 -GGCCTCGA TGCGCTTCCGCTTCA-3 0 (antisense) for A-1744G, and the restriction enzymes were AluI, HpaII, and PstI, respectively.…”
Section: Genotypingmentioning
confidence: 99%